Fetal thyroid hyperplasia, rhesus isoimmunisation, and amniography. Issue 3 (March 1980) - Becroft, D M; Smeeton, W M; Stewart, J H
Abstract : Thyroid hyperplasia was identified at necropsy in 16 of 70 cases of haemolytic disease of the newborn due to rhesus isoimmunisation dying in the years 1959--76. No hyperplasia was found in the thyroids from 140 nonrhesus-affected infants matched for date of birth, bodyweight and length, and gestation, or in cases of haemolytic disease born before 1966. All 16 infants with thyroid hyperplasia had received intrauterine transfusions and the iodine-containing contrast media used for preliminary amniography were the only goitrogenic factors identified. Lipiodol, first used in 1966, was considered to have the greatest effect. The 16 infants with hyperplastic thyroids were less mature and smaller than 22 infants with normal thyroids who had been similarly exposed to contrast media. The high incidence of hyperplasia may be due to immaturity of the adaptive mechanisms which allow most normal individuals to escape the goitrogenic effects of iodine compounds.